The clinical and prognostic role of changes in parameters of the hemostasis system and C-reactive protein in the development of thrombotic complications in oxygen-dependent patients with coronavirus disease (COVID-19) - Cherkaskyi, V. V.; Riabokon, O. V.; Riabokon, Yu. Yu.; Черкаський, Володимир Васильович; Рябоконь, Олена Вячеславівна; Рябоконь, Юрій Юрійович (Запорізький державний медичний університет, 2023)
C-reactive protein (CRP) in the development of thrombotic complications in oxygen-dependent patients with coronavirus disease (COVID-19). Materials and methods. 211 oxygen-dependent patients with COVID-19 were examined. To assess the prognostic role of changes in hemostasis parameters and CRP, patients were divided into groups: I group – 94 patients who recovered, II group – 117 patients who died. Subgroups: II-A subgroup – 35 patients with thrombotic complications and II-B subgroup – 82 patients without these complications. All patients were examined and received treatment according to the normative documents in force at the relevant time. Results. The frequency of thrombotic complications in oxygen-dependent patients with COVID-19 was 16.6 %, among which the most common were pulmonary embolism (6.6 %), myocardial infarction (6.2 %), and ischemic stroke (3.2 %). Lifetime diagnosis of thrombotic complications took place on the 18th [16.0; 24.0] day of illness in 45.9 % of cases. Deathtime diagnosis of thrombotic complications took place on the 24th [20.0; 28.0] day of illness in 54.1 % of cases. Lifetime pulmonary artery thromboembolism was diagnosed less frequently than ischemic stroke (p = 0.002) and myocardial infarction (p = 0.02). Мета роботи – з’ясувати клініко-прогностичну роль змін параметрів гемостазу та С-реактивного протеїну (СРП) в розвитку тромботичних ускладнень у кисневозалежних хворих на коронавірусну хворобу (COVID-19). Матеріали та методи. Обстежено 211 кисневозалежних хворих на COVID-19. Для оцінювання прогностичної ролі змін параметрів гемостазу та СРП пацієнтів поділили на групи: І – 94 хворих, які одужали; ІІ – 117 осіб, які померли. Підгрупи пацієнтів: ІІ-А – 35 хворих із тромботичними ускладненнями; ІІ-В підгрупа – 82 особи без таких ускладнень. Усіх хворих обстежили, призначили лікування згідно з чинними на той час нормативними документами. Результати. Частота виникнення тромботичних ускладнень у кисневозалежних хворих на COVID-19 становила 16,6 %. Найчастіші з-поміж них – тромбоемболія легеневої артерії (6,6 %), інфаркт міокарда (6,2 %), ішемічний інсульт (3,2 %). Прижиттєва діагностика тромботичних ускладнень відбулася на 18 [16,0; 24,0] день хвороби в 45,9 % випадків. По- смертна діагностика тромботичних ускладнень – на 24,0 [20,0; 28,0] день хвороби в 54,1 % випадків. Тромбоемболію легеневої артерії прижиттєво діагностували рідше, ніж ішемічний інсульт (р = 0,002) та інфаркт міокарда (р = 0,02).
Клініко-прогностична роль змін параметрів системи гемостазу та С-реактивного протеїну в розвитку тромботичних ускладнень у кисневозалежних хворих на коронавірусну хворобу (COVID-19)
Cherkaskyi V. V. - ORCID ID: 0000-0003-2959-8803; Riabokon O. V. - ORCID ID: 0000-0002-7394-4649; Riabokon Yu. Yu. - ORCID ID: 0000-0002-2273-8511.
Keywords: COVID-19; viral infection; thrombotic complications; diagnosis; hemostasis; C-reactive protein; risk factors; prognosis; вірусна інфекція; тромботичні ускладнення; діагностика; гемостаз; С-реактивний протеїн; фактори ризику; прогноз